Meta‐analysis of yield and nitrous oxide outcomes for nitrogen management in agriculture - Maaz, Tai M.; Sapkota, Tek B.; Eagle, Alison J.; Kantar, Michael B.; Bruulsema, Tom W.; Majumdar, Kaushik (Global change biology, 2021)
Improved nitrogen (N) use is key to future food security and environmental sustainability. While many regions still experience N shortages, agriculture is the leading global emitter of N2O due to losses exacerbated by N surpluses in other regions. In order to sustainably maintain or increase food production, farmers and their advisors need a comprehensive and actionable understanding of how nutrient management affects both yield and N2O emissions, particularly in tropical and subtropical agroecosystems. We performed a meta‐analysis to determine the effect of N management and other factors on N2O emissions, plant N uptake, and yield. Our analysis demonstrates that performance indicators—partial N balance and partial factor productivity—predicted N2O emissions as well as or better than N rate. While we observed consistent production and environmental benefits with enhanced‐efficiency fertilizers, we noted potential trade‐offs between yield and N2O emissions for fertilizer placement. Furthermore, we observed confounding effects due to management dynamics that co‐vary with nutrient application practices, thus challenging the interpretation of the effect of specific practices such as fertilization frequency. Therefore, rather than providing universally prescriptive management for N2O emission reduction, our evidence supports mitigation strategies based upon tailored nutrient management approaches that keep N balances within safe limits, so as to minimize N2O emissions while still achieving high crop yields. The limited evidence available suggests that these relationships hold for temperate, tropical, and subtropical regions, but given the potential for expansion of N use in crop production, further N2O data collection should be prioritized in under‐represented regions such as Sub‐Saharan Africa. Our findings show that, unlike many soil and climate variables, fertilizer management had consistent impacts on crop yields and N2O emissions with potential synergies and trade‐offs. Our evidence supports mitigation strategies based upon tailored nutrient management approaches that keep N balances within safe limits, so as to minimize N2O emissions while still achieving high crop yields. Practices that enhance partial factor productivity of N can result in lower N2O emissions for a given level of productivity and “shift” the exponential increase in N2O emissions as productivity increases.